TINJAUAN PENGENDALIAN LIMBAH PUPUK DALAM RANGKA PENERAPAN SISTEM MANAJEMEN LINGKUNGAN DI PT. PETROKIMIA GRESIK - Susetyorini, Susetyorini; Hariadi, Slamet (GEMA EKONOMI, 2017)
Environmental problems that we now face have range and the trait of being global. Recently many countries, advanced economic implement a policy development of living environment internationally. As for the purpose of this research is to review and analyzes application of the System Management of the Environment (SML) based on ISO 14001 in PT. Petrokimia Gresik and to know the obstacles found in the Implementation of the Management of the Environment (SML) based on ISO 14001 in PT. Petrokimia Gresik. This research used the Methodology Qualitative. The kind of data that in use in research is primary andsecondary data. This research is Explorative for research it is associated with questions ? what ?. Hence, target researchers is to memformulasi some questions that having precision research will come can respond to. Data analysis begins with conducting in-depth interviews with informants. After interviewing, researchers make transkip the results of interviews with circuitous way back recording interviews with circuitous way back recording the interview. After the researchers wrote the results of interviews into transkip, next researchers make reduction data by means of abstraction, namely take an appropriate data to the context research and ignore the necessary data. The result of this research draw a line straight the theory ISO 14001 of the Management of the Environment applied by PT. Petrokimia Gresik to the fact that is he in accordance with the and laws.All employees had participate in manifesting love environment be culture work harmonious between productivity with wisdom nature. A lot of innovation produced by an employee of PT. Petrokimia Gresik for Manifesting Love Environment with the Competition Fire on the Moon K3 National, 5R Competition, competition or preparedness emergency. But it is possible that PT.Petrokimia Gresik is chemical company that have been constructed for 45 Years where productionlevel still in sued to reach production maximum will but thecompany old with age, although there had been improvements every day but it is possible that there are still any waste products that passes from the Implementation of the Management of the Environment. Not to forget also that every the Implementation of the Management of the Environment going to need a charge that is great in a factory and care training human resources. Let alone the costs of compensation for residents in one neighborhood ring Companies and Maintenance and the Maintenance of a plant which issued by the company. DOI : 10.5281/zenodo.3477665